Evidence of a corona discharge induced by natural high voltage due to vertical potential gradient. (18th February 2019) - Hong, D; Rabat, H; Kirkpatrick, M J; Odic, E; Merbahi, N; Giacomoni, J; Eichwald, O
Abstract: This paper describes a study evidencing the creation of a corona discharge induced by natural high voltage found above the Earth's surface due to the vertical potential gradient at an altitude of 125 meters. Experiments were made in fine weather in autumn and with little wind, on the Balloon Generali, a tethered helium balloon that takes tourists up for views above Paris. The measuring equipment was installed in the gondola suspended from the tethered balloon. A metal point electrode was also suspended from the balloon at the same level as the gondola at a lateral distance of 8 m. During the ascent, as soon as the altitude of the gondola exceeded about 65 m, a current coming from the metal point electrode was detected. The value of this current fluctuated but generally increased with height and reached an intensity of up to 320 nA at 125 m. When the electrode tip approached the gondola, which was electrically grounded via the pull cable, the current was lower; when the tip was replaced by a larger rounded electrode, the current was observed to disappear. The combination of these observations clearly demonstrated the presence of a corona discharge caused by the vertical potential gradient, and in turn, the existence of a corona discharge without high voltage power supply evidenced the obtaining of a natural high voltage.